Effect of resveratrol supplementation to Triladyl® on the quality of ram chilled semen - AL-MUTARY, MOHSEN (The Indian Journal of Animal Sciences, 2019)
The present investigation aimed to estimate the in vitro effects of resveratrol (RES) on the quality of chilled ram semen. Resveratrol was added to Triladyl® in three different concentration as 0 (control), 200 or 400 μM. Semen was collected from three Najdi rams, pooled and extended with one of three previous extenders for a final concentration of 600×106 sperm/ml. Then, the diluted semen was cooled gradually, and stored at 4°C. The total motility, viability, plasma membrane integrity and acrosome integrity were assessed at 0, 24, 72 and 120 h of storage. The thermal incubation test was evaluated at day 7. The survival time, total motility and the progressive motility were registered at day 15 of storage. After 4 h of incubation, the percentage of live sperm was significantly lower in the control group than in other groups. Results of survival time, total motility and progressive motility at day 15 of liquid storage were significantly higher in RES groups than that of the control. Based on the results of incubation resistance, survival time, total and progressive motility, it could be concluded that adding 200 and 400 μM of RES to Triladyl extender can improve the quality of ram semen during chilled storage at 4°C.